CATION ORDERING IN ORTHOPYROXENES FROM TWO STONY-IRON METEORITES: IMPLICATIONS FOR COOLING RATES AND METAL-SILICATE MIXING - Ganguly J.; Stimpfl M. (My University, 2000)
We have determined the cooling rates of orthopyroxene crystals from two group IVA stony iron meteorites-Steinbach (ST) and Sao Joao Nepomuceno (SJN)-on the basis of their Fe-Mg ordering states. The rate constant was calibrated as a function of temperature by controlled cooling experiments using orthopyroxene crystals separated from ST. These data were used along with earlier calibrations of the equilibrium intracrystalline fractionation of Fe and Mg as a function of temperature for crystals separated from both meteorites to calculate their cooling rates. The site occupancies of the orthopyroxene crystals were determined by single-crystal X-ray diffraction subject to the bulk compositional constraints. The closure temperatures (Tc) of cation ordering for the untreated crystals from SJN are ~400°C, whereas those from ST vary between ~430 and 470°C. Reconciliation of the metallographic and orthopyroxene cooling rate data, within the framework of the metal-silicate mixing model of Haack et al. (1995), suggests that these two stony irons had cooled at a similar rate of ~400°C/Ma through the closure temperatures for cation ordering in the orthopyroxenes. This was followed by slow cooling for ST at ~50°C/Ma at T < 425°C. Similar slow cooling was not recorded by the metals in SJN, which implies that if this stony iron were subjected to slow cooling, it must have been below 350°C. The similar cooling rates above 425°C for both ST and SJN, as required to reconcile the metal and orthopyroxene cooling rate data, is at variance with the earlier notion (Rasmussen et al., 1995) of distinctly different cooling rates for the high and low Ni IVA irons and stony irons. The cation ordering and metallographic cooling rate data are also amenable to an alternative interpretation, which requires two different parent bodies for the two stony irons, and mixing of the metal and silicate components of ST after the metals had cooled below the closure temperature of Fe-Ni interdiffusion. However, the available textural data for ST seems to argue against such metal-silicate mixing model.